School Culture Program: Implementation of School Innovation in the Disruption Era in SDIT Anak Sholeh Mataram Lombok - Emawati (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
This study aims to explore the innovations of Islamic schools in Lombok in the face of the disruption era. SDIT Anak Sholeh Mataram is a representation of a school that made the innovation effort. Data were obtained using the methods of observation, interviews, and documentation. Meanwhile, the theory used to analyze the problem in this study is to adapt the theory of